PELAKSANAAN PENITIPAN ANAK NARAPIDANA USIA 2 TAHUN DI LEMBAGA PEMASYARAKATAN PEREMPUAN KELAS II A SUNGGUMINASA PERSPEKTIF SIYASAH SYAR’IYYAH - Melati, Rima; Sahroh (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2024)
This study aims to describe the implementation of child care for convicts aged 2 years at the class II A Sungguminasa women's correctional institution from the perspective of siyasah syar'iyyah. In answering these problems, the author uses a normative syar`i approach and a normative juridical approach. The method of data collection is done by way of interviews, observation, documentation, and literature study. The results of the study show that the mechanism for implementing child care under the age of 2 years at the Class II A Sungguminasa women's correctional institution is running as it should where the rights and obligations of convicts have been fulfilled because it is in accordance with law number 22 of 2022 concerning correctional facilities. Legal protection for 2-year-old child convicts at Sungguminasa Class II A Correctional Institution convicts of 2-year-old child care at the Sungguminasa class II A women's correctional institution are maximized because they have protected and maintained according to the rules issued. Siyasa Syariyyah's view of the implementation of day care for children aged 2 years in prison has carried out its responsibilities properly, through the services provided it is also good for children and according to the mandate as in surah An-Nisa verses 58 and 59, namely the child as a mandate or entrustment that must be best guarded. Their rights are fulfilled, loved, cared for, educated so that they have a bright future and make their parents happy.